A Comparative Kinetic Study of Chalcopyrite Leaching Using Alternative Oxidants in Methanesulfonic Acid System. (3rd April 2022) - Ahn, Junmo; Wu, Jiajia; Lee, Jaeheon
ABSTRACT: Methanesulfonic acid was proven to be an alternative lixiviant for copper leaching from chalcopyrite with hydrogen peroxide as an oxidant. Two alternative oxidants, dichromate and nitrate, were studied for the copper dissolution from chalcopyrite, a refractory copper sulfide mineral. During chalcopyrite leaching tests, both oxidants achieved the copper extraction above 90% in 30 g/L methanesulfonic acid at 75 o C. The activation energies in dichromate and nitrate leaching systems were 23 and 43 kJ/mol, classified as mass transfer and chemical reaction-controlled mechanism, respectively. The XRD analysis of a leached residue showed a formation of K-Cr-jarosite from methanesulfonic acid-dichromate system. Methanesulfonic acid with nitrate leaching system could be the most effective and sustainable for chalcopyrite leaching based on the comparative investigation.